The Role of Everyday Contexts in Learner-centred Teaching: The practice in Namibian secondary schools - Kasanda, Choshi; Lubben, Fred; Gaoseb, Noah; Kandjeo-Marenga, Utji; Kapenda, Hileni; Campbell, Bob (International journal of science education, 2005)
This paper reports on the use of out-of-school everyday contexts in Namibian science classrooms. This use is portrayed against the backdrop of an explicit educational philosophy of learner-centred teaching. Data were collected through audio-taped teacher-learner interactions and non-participant field notes in 29 junior and senior science classes taught by 12 teachers in six schools. An existing typology was applied to classify episodes of use of everyday contexts and identify teachers' pedagogic strategies for their use. The results show that more everyday contexts are used in junior secondary than in senior secondary classes, that only a limited range of types of everyday contexts are used at both levels, and that their use often follows theoretical exposition or teacher questioning. These findings are related to three interpretations of learner-centred teaching. Recommendations for a fuller implementation of learner-centred teaching are made.